Analysis of risk factors affecting the postoperative drainage after a laparoscopic partial nephrectomy: a retrospective study - Tian, Yi-Qun; Ren, Xiang; Yin, Yi-Sheng; Wang, Jing; Li, Xing; Guo, Zi-Hao; Zeng, Xiao-Yong (Frontiers in Medicine, 2024)
Purpose Laparoscopic partial nephrectomy (LPN) remains the most commonly used measure for treating localized renal cell cancer (RCC) with an increasing incidence of RCC ever since the 1990s. This study aimed to identify risk factors that affect the postoperative time of drainage and total drainage volume after LPN. Method The clinical data of 612 RCC patients who received LPN from January 2012 to December 2022 in our hospital, including the postoperative drainage time and total drainage volume, were retrospectively analyzed. Univariable and multivariable linear regression and correlation analyses were used to identify the correlations between 21 factors, which include gender, age, history of alcohol consumption, family history of RCC, body weight, body mass index (BMI), and operation time, postoperative drainage time, and total drainage volume. Results The mean time of drainage was 3.52 ± 0.71 days (range: 2 to 8 days), with an average total drainage volume of 259.83 ± 72.64 mL (range: 50 to 620 mL). Both univariable and multivariable linear regression analyses revealed several statistically significant associations. Gender (p = 0.04), age (p = 0.008), smoking history (p < 0.001), diabetes (p = 0.032), operation time (p = 0.014), and BMI (p = 0.023) were identified as significant factors associated with the time of drainage. On the other hand, age (p = 0.008), smoking history (p < 0.001), diabetes (p = 0.006), and BMI (p = 0.016) emerged as independent risk factors influencing the total drainage volume. Conclusion The duration of postoperative drainage was found to be associated with gender, age, smoking history, diabetes, operation time, and BMI. In contrast, the total drainage volume was primarily influenced by age, smoking history, diabetes, and high BMI following LPN. For patients with these conditions, meticulous attention to hemostasis and bleeding control is crucial during the perioperative period.